Pemberdayaan Masyarakat Desa Sukanagara melalui Penguatan Potensi Kerajinan Bambu dan Pertanian Organik Berbasis Kearifan Lokal - Nurul Frasiska; Nazna Ramdani Putra; Roihan Salsabila (Universitas Perjuangan Tasikmalaya, 2026)
This community service activity was carried out in Sukanagara Village, Tanjungjaya District, Tasikmalaya Regency, through the 2025 Community Service Program (Kuliah Kerja Nyata, KKN) of Universitas Perjuangan Tasikmalaya. The aim was to empower the local community by strengthening local potentials in bamboo handicrafts and organic farming. The methods applied included participatory observation, interviews, socialization, training, and direct community assistance. The results showed improved skills among residents in managing bamboo weaving businesses through digital marketing training using Google Business Profile, as well as increased awareness of environmentally friendly farming through compost production training using livestock waste. The program also strengthened socio-economic networks and encouraged intergenerational collaboration in preserving local wisdom. Overall, this activity had a positive impact on the community’s economic, social, and ecological capacities. The empowerment model based on local potential and wisdom developed in this program can be replicated in other rural areas with similar characteristics.